2019
DOI: 10.1093/aje/kwz147
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Effectiveness of State-Level Tuberculosis Interventions in California, Florida, New York, and Texas: A Model-Based Analysis

Abstract: The incidence of tuberculosis (TB) in the United States has stabilized, and additional interventions are needed to make progress toward TB elimination. However, the impact of such interventions depends on local demography and the heterogeneity of populations at risk. Using state-level individual-based TB transmission models calibrated to California, Florida, New York, and Texas, we modeled 2 TB interventions: 1) increased targeted testing and treatment (TTT) of high-risk populations, including people who are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…18 Although the effectiveness and cost effectiveness of targeting prevention efforts to specific populations differ by state, 19,20 JHU estimated that targeting LTBI testing and treatment to half of the non-US-born population in these 4 states could lower national TB incidence by 25% to 31% during the next 10 years. 21 LTBI testing and treatment delivered to less numerous populations with higher-than-average TB risk (eg, persons with HIV) was more efficient than LTBI testing and treatment of non-US-born persons but did not substantially reduce TB incidence in the United States. 21 The most-to-least cost-effective populations to test and treat were: persons with HIV, non-US-born persons, persons experiencing homelessness, incarcerated persons, and persons with diabetes.…”
Section: Which Populations To Test and Treatmentioning
confidence: 95%
See 4 more Smart Citations
“…18 Although the effectiveness and cost effectiveness of targeting prevention efforts to specific populations differ by state, 19,20 JHU estimated that targeting LTBI testing and treatment to half of the non-US-born population in these 4 states could lower national TB incidence by 25% to 31% during the next 10 years. 21 LTBI testing and treatment delivered to less numerous populations with higher-than-average TB risk (eg, persons with HIV) was more efficient than LTBI testing and treatment of non-US-born persons but did not substantially reduce TB incidence in the United States. 21 The most-to-least cost-effective populations to test and treat were: persons with HIV, non-US-born persons, persons experiencing homelessness, incarcerated persons, and persons with diabetes.…”
Section: Which Populations To Test and Treatmentioning
confidence: 95%
“…21 LTBI testing and treatment delivered to less numerous populations with higher-than-average TB risk (eg, persons with HIV) was more efficient than LTBI testing and treatment of non-US-born persons but did not substantially reduce TB incidence in the United States. 21 The most-to-least cost-effective populations to test and treat were: persons with HIV, non-US-born persons, persons experiencing homelessness, incarcerated persons, and persons with diabetes. 20 JHU concluded that only by providing interventions to non-US-born persons could substantial reductions in TB incidence be made.…”
Section: Which Populations To Test and Treatmentioning
confidence: 95%
See 3 more Smart Citations